Problems of Teaching and Learning English as a Foreign Language in South Yemen: A Case Study of Lahj Governorate - Sabri Thabit Saleh Ahmed; Bushra Thabit Ahmed Qasem (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The task of teaching and learning English as a foreign language is not an easy task as there are many factors that may contribute positively or negatively to its success. In the context of this study, most school-leavers have very poor English, especially when looking at their oral skills. This indicates that there are some problems that EFL learning and teaching encounter, and then such problems are reflected in students’ proficiency level. This study, therefore, explored the problems encountering EFL teaching and learning in Lahj primary and secondary schools to identify such problems and suggest some solutions that may help in improving English language teaching and learning in the concerned schools. Data were collected from 32 EFL senior teachers and supervisors of Lahj governorate. Findings showed that large classes, lack of teaching aids, teachers’ low proficiency in English, teachers’ limited experience with communicative language teaching, late beginning of learning English, lack of focus on oral communicative English, use of mother tongue in classroom, students’ low motivation and interference between English and Arabic are considered as major problems encountering English language teaching and learning in the concerned South Yemeni schools and contribute negatively to students’ proficiency level. The study has provided some recommendations that may help in improving EFL teaching and learning in the concerned schools and in Yemeni schools generally.